Why create government corporations? An examination of the determinants of corporatization in the Canadian public sector. (21st October 2021) - Bernier, Luc; Juillet, Luc; Deschamps, Carl
Abstract: Public corporations have grown in popularity over the last 30 years, but the conditions that lead governments to create them are still debated. In this study, we draw on an original dataset of public organizations at the federal and provincial levels in Canada to test the prevalence of corporatization and the conditions associated with the creation of public corporations. Our results show that corporatization has been an important phenomenon in Canada over the last 30 years, but that the creation of public corporations is not associated with pressures on public finances or favored by right‐wing governments. Our main finding is that the creation of public corporations is mainly associated with administrative capacity. Our results suggest that corporatization may be more a pragmatic exercise in state‐building than an ideological or New Public Management (NPM)‐driven project, but that its cost or complexity may make it more accessible to larger administrations. Résumé: Le recours aux corporations publiques a gagné en popularité au cours des trente dernières années, mais les conditions qui amènent les gouvernements à faire ce choix restent à préciser. Dans cette étude, nous nous appuyons sur des données originales aux niveaux provincial et fédéral au Canada pour tester ce qui explique le choix de la corporatisation. Nos résultats montrent que celle‐ci a été un phénomène important durant cette période. Nous constatons toutefois que la création de corporations publiques n'est pas associée à des raisons de finances publiques ou à la présence de gouvernements de droite, mais surtout à la capacité administrative des administrations. Nos résultats suggèrent que la corporatisation est moins un projet idéologique qu'un choix pragmatique visant le renforcement et la construction de l'État, mais que son coût ou sa complexité peuvent rendre cette approche plus accessible aux plus grandes administrations.